45S5 bioactive glass coatings by atmospheric plasma spraying obtained from feedstocks prepared by different routes - Lopez Calvo, Veronica; Vicent Cabedo, Monica; Bannier, Emilie; Canas Recacha, Eugeni; Boccaccini, Aldo R.; Cordero Arias, Luis Eduardo; Sanchez Vilches, Enrique (Journal of Materials Science, 2014)
45S5 bioactive glass powders with the composition of 45 SiO, 6 PO, 24.5 CaO and 24.5 wt% NaO were melted and quenched in water to obtain a frit. The frit was milled using two different routes: dry milling followed by sieving to obtain glass particles and wet milling followed by spray drying to obtain a powder comprising porous agglomerates. All feedstocks showed adequate characteristics that make them suitable to be deposited by atmospheric plasma spraying. The powders and coatings were characterised by field-emission gun environmental scanning electron microscope and X-ray diffraction. The roughness and the contact angle of the coatings were also determined. The bioactivity of the powders and coatings was assessed by immersion in simulated body fluid. It was found that bioactive glass prepared from bioglass frit by dry milling exhibited similar bioactivity as that of a commercial bioactive glass. All coatings produced showed good adhesion to the substrate as well as suitable surface properties to ensure efficient contact with body fluid. Regardless of the characteristics of the feedstocks or plasma spray conditions used, all coatings were exclusively made up of an amorphous phase. On the other hand, micrographs revealed that the characteristics of the feedstock strongly impact on the final coating microstructure. The most homogeneous microstructure was obtained when the feedstock was prepared by fine dry grinding of the frit. For this coating, the formation of a bioactive layer was also proved by Fourier transform infrared spectroscopy and X-ray diffraction.

Alginate/Bioglass® composite coatings on stainless steel deposited by direct current and alternating current electrophoretic deposition - Chen, Qiang; Cordero Arias, Luis Eduardo; Roether, Judith; Cabanas Polo, Sandra; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Surface & Coatings Technology, 2013)
Direct current (DC) and alternating current (AC) electrophoretic deposition (EPD) approaches involving different number of EPD cycles were developed for the fabrication of alginate/Bioglass® composite coatings from water-based suspensions. The high stability of the colloidal suspension was confirmed by zeta-potential assessment and the properties of coatings deposited from both DC-EPD and AC-EPD were quantitatively compared by using a range of characterization methods. The deposition yield and coating composition were determined by mass and thermogravimetric analysis. Coatings with different microstructure and thickness were observed by scanning electron microscopy. Significant differences in surface roughness and hydrophilicity (determined by water contact angle measurement) of coatings obtained by DC-EPD and AC-EPD were identified and discussed. The coating adhesion strength and corrosion resistance were evaluated by standard tape test and electrochemical method, respectively, and the experimental data showed the superior adhesion and corrosion resistance of AC-EPD coatings compared to DC-EPD coatings. In order to investigate the in vitro bioactivity, all coatings were immersed in simulated body fluid for 7. days. Results from Fourier transform infrared spectroscopy (FTIR) analysis showed the typical characteristic peaks of hydroxyapatite formed on both DC- and AC-EPD coatings. Based on the results of this study, bioactive alginate/Bioglass® coatings are proposed as suitable candidates for applications in dental and orthopedic metallic implants and for bone tissue scaffolds. © 2013 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.algina
Keywords: Alginate; Bioactive glass; Bioactivity; Biomedical coatings; Electrophoretic deposition

Biocompatible ceramic-biopolymer coatings obtained by electrophoretic deposition on electron beam structured titanium alloy surfaces - Ramskogler, C.; Cordero, Luis; Warchomicka, F.; Boccaccini, Aldo R.; Sommitsch, C. (Materials Science Forum, 2017)
An area of major interest in biomedical engineering is currently the development of improved materials for medical implants. Research efforts are being focused on the investigation of surface modification methods for metallic prostheses due to the fundamental bioinert character of these materials and the possible ion release from their surfaces, which could potentially induce the interfacial loosening of devices after implantation. Electron beam (EB) structuring is a novel technique to control the surface topography in metals. Electrophoretic deposition (EPD) offers the feasibility to deposit at room temperature a variety of materials on conductive substrates from colloidal suspensions under electric fields. In this work single layers of chitosan composite coatings containing titania nanoparticles (n-TiO2) were deposit by EPD on electron beam (EB) structured Ti6Al4V titanium alloy. Surface structures were designed following different criteria in order to develop specific topography on the Ti6Al4V substrate. n-TiO2 particles were used as a model particle in order to demonstrate the versatility of the proposed technique for achieving homogenous chitosan based coatings on structured surfaces. A linear relation between EPD time and deposition yield on different patterned Ti6Al4V surfaces was determined under constant voltage conditions, obtaining homogeneous EPD coatings which replicate the 3D structure (pattern) of the substrate surface. The present results show that a combination of both techniques can be considered a promising surface modification approach for metallic implants, which should lead to improved interaction between the implant surface and the biological environment for orthopaedic applications.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Electron beam structuring; Electrophoretic deposition; N-TiO2/chitosan; Ti6Al4V

Electrochemical behavior of nanostructured TiO2/alginate composite coating on magnesium alloy AZ91D via electrophoretic deposition - Cordero Arias, Luis Eduardo; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Surface & Coatings Technology, 2015)

Electrochemical investigations of magnesium in DMEM with biodegradable polycaprolactone coating as corrosion barrier - Degner, Julia; Singer, Ferdinand; Cordero, Luis; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Applied Surface Science, 2013)
Magnesium and its alloys are being increasingly investigated as biodegradable metallic implant materials. However, the high corrosion rate and accumulation of hydrogen gas upon degradation prevent the clinical application of many magnesium based materials. Applying polymer or ceramic coatings is a popular approach to improve the corrosion behaviour of magnesium and its alloys. In the current research, a biodegradable polymer film of polycaprolactone (PCL) is prepared in different concentrations by spin coating, in order to influence the corrosion behaviour of 99.9% pure magnesium. The resulting polymer coating was qualified by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and tape-test according to ASTM D3359-09 to measure the adhesion strength of the coating on the substrate. Furthermore, coated and uncoated specimens were stored up to 30 days at 37 ÌŠC in DMEM. The corrosion behaviour was investigated by polarization curves. The PCL-films were found to be uniform and without pores, but they show a low adhesion strength on the substrate. Nevertheless, remarkable improvement of the corrosion resistance of magnesium substrate can be obtained by the polymer films, depending on the film thickness and exposition time. In summary, coating magnesium with PCL is a promising method to tailor the degradation behaviour for biomedical applications. © 2013 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.electr_2
Keywords: Biodegradable; Coating; Corrosion; DMEM; FTIR; Magnesium; Polycaprolactone

Electrophoretic deposition of cellulose nanocrystals (CNs) and CNs/alginate nanocomposite coatings and free standing membranes - Chen, Qiang; Perez De Larraya, Uxua; Garmendia, Nere; Lasheras-Zubiate, Maria; Cordero Arias, Luis Eduardo; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Colloids and Surfaces B: Biointerfaces, 2014)

Electrophoretic Deposition of Chitosan/45S5 Bioactive Glass Composite Coatings Doped with Zn and Sr - Miola, Marta; Verne, Enrica; Ciraldo, Francesca; Cordero Arias, Luis Eduardo; Boccaccini, Aldo R. (Frontiers in Bioengineering and Biotechnology, 2015)

Electrophoretic deposition of chitosan/h-BN and chitosan/h-BN/TiO2 composite coatings on stainless steel (316L) substrates - Raddaha, Namir S.; Cordero Arias, Luis Eduardo; Cabanas Polo, Sandra; Virtanen, Sannakaisa; Roether, Judith; Boccaccini, Aldo R. (Materials, 2014)

Electrophoretic deposition of chondroitin sulfate-chitosan/bioactive glass composite coatings with multilayer design - Cordero Arias, Luis Eduardo; Boccaccini, Aldo R. (Surface & Coatings Technology, 2017)
Keywords: Bioactive glass; Chitosan; Chondroitin sulfate; Coating; Electrophoretic deposition (EPD)

Electrophoretic deposition of composite coatings based on alginate matrix/45S5 bioactive glass particles doped with B, Zn or Sr - Miola, Marta; Cordero Arias, Luis Eduardo; Ferlenda, Giulia; Cochis, Andrea; Virtanen, Sannakaisa; Rimondini, Lia; Verné, Enrica; Boccaccini, Aldo R. (Surface & Coatings Technology, 2021)
In this research work composite coatings made of alginate and 45S5 bioactive glass particles doped with B, Zn or Sr were synthesized by means of electrophoretic deposition and characterized from morphological, compositional, thermogravimetric, mechanical and electrochemical points of view. The developed coatings were also subjected to in vitro test in SBF solution to evaluate their ability to induce hydroxyapatite precipitation and cytocompatibility evaluation using human primary fibroblasts. The obtained results demonstrated a good homogeneity of the coatings, high adhesion and a protective behavior towards the substrate. The thermogravimetric analysis proved that the glass amount was constant before and after the deposition and all the investigated coatings promoted the deposition of hydroxyapatite but with different kinetics. Since the Zn containing coating showed the best bioactive behavior it was subjected to cytocompatibility test, which demonstrated, after an initial reduction of cell viability, a good cell proliferation and the production of collagen from the ECM. These findings suggest that the obtained coatings are promising materials to coat metallic prosthetic devices.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Alginate; Bioactive glasses; Composite coatings; Electrophoretic deposition

Electrophoretic deposition of nanostructured TiO2/alginate and TiO2-bioactive glass/alginate composite coatings on stainless steel - Cordero Arias, Luis Eduardo; Cabanas Polo, Sandra; Gilabert, J.; Goudouri, Ourania Menti; Sanchez, E.; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Advances in Applied Ceramics, 2014)
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.electr_1

Electrophoretic deposition of nanostructured-TiO2/chitosan composite coatings on stainless steel - Cordero Arias, Luis Eduardo; Cabanas Polo, Sandra; Gao, Haoxiang; Gilabert, J.; Sanchez, E.; Roether, Judith; Schubert, Dirk W.; Virtanen, Sannakaisa; Boccaccini, Aldo R. (RSC Advances, 2013)
Novel chitosan composite coatings containing titania nanoparticles (n-TiO2) for biomedical applications were developed by electrophoretic deposition (EPD) from ethanol–water suspensions. The optimal ethanol–water ratio was studied in order to avoid bubble formation during the EPD process and to ensure homogeneous coatings. Different n-TiO2 contents (0.5–10 g L−1) were studied for a fixed chitosan concentration (0.5 g L−1) and the properties of the electrophoretic coatings obtained were characterized. Coating composition was analyzed by thermogravimetric analysis (TG), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis. Scanning electron microscopy (SEM) was employed to study both the surface and the cross section morphology of the coatings, and the thicknesses (2–6 μm) of the obtained coatings were correlated with the initial ceramic content. Contact angle measurements, as a preliminary study to predict hypothetic protein attachment on the coatings, were performed for different samples and the influence of a second chitosan layer on top of the coatings was also tested. Finally, the electrochemical behavior of the coatings, evaluated by polarization curves in DMEM at 37 °C, was studied in order to assess the corrosion resistance provided by the n-TiO2/chitosan coating
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.electr

Electrophoretic deposition of nanostructured titania-bioactive glass/alginate coatings on stainless steel - Cordero Arias, Luis Eduardo; Cabanas Polo, Sandra; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Key Engineering Materials, 2015)

Electrophoretic deposition of organic/inorganic composite coatings containing ZnO nanoparticles exhibiting antibacterial properties - Karbowniczek, Joanna; Cordero Arias, Luis Eduardo; Virtanen, Sannakaisa; Misra, Superb K.; Valsami-Jones, Eugenia; Tuchscherr, Lorena; Rutkowski, Bogdan; Gorecki, Kamil; Bala, Piotr; Czyrska-Filemonowicz, Aleksandra; Boccaccini, Aldo R. (Materials Science and Engineering C, 2017)
Keywords: Antibacterial surfaces; Bioactive glass; Chitosan; Coatings; Electrophoretic deposition; ZnO nanoparticles

Electrophoretic deposition of organic/inorganic composite coatings on metallic substrates for bone replacement applications: mechanisms and development of new bioactive materials based on polysaccharides - Cordero Arias, Luis Eduardo (2015)
Regarding the need to improve the usually encountered osteointegration of metallic implants with the surrounding body tissue in bone replacement applications, bioactive organic/inorganic composite coatings on metallic substrates were developed in this work using electrophoretic deposition (EPD) as coating technology. In the present work three polysaccharides, namely alginate, chondroitin sulfate and chitosan were used as the organic part, acting as the matrix of the coating and enabling the coating attachment to the metallic substrates (stainless steel AISI 316L, titanium alloy TI6Al4V and magnesium alloy AD91D). Different types of ceramic fillers were investigated as the inorganic phase of the coatings. Different bioactive glasses were used to impart osteoconductive and osteoinductive properties to the coating, while nanoparticles of titania and zinc oxide were used to bring antibacterial properties, improve the mechanical stability and control the degradation behavior of the coatings.In this work the possibility to develop stable suitable suspensions to produce coatings by EPD is shown, based in the three selected biopolymers and containing one or more types of ceramic particles in different size ranges from 20 nm to 30 µm. The investigation of different solvents for EPD, namely water and ethanol, was carried out (single or in mixtures of both) to develop stable suspensions to reduce the negative effect of the water hydrolysis in the coating morphology. The suspension stability was studied via ζ–potential measurements finding that the suspension mechanism is controlled by the polymer, which, by esterification effect, suspends the ceramic particles in the liquid media.A variety of more than 20 coatings were studied and developed during this thesis. The major goal was to develop suitable EPD technology to produce coatings with: adequate (i) homogeneity, (ii) attachment to the substrate, (iii) ceramic/polymer ratio, (iv) wettability and morphology, (v) electrochemical behavior, (vi) bioactivity and (vi) degradation behavior. Other properties were also analyzed such as: antibacterial activity and drug delivery function (by incorporation of simvastatin).Alginate based coatings containing nanoparticles of TiO2 or ZnO were developed by anodic EPD. Bioactive glass 45S5® (BG) was successfully incorporated to those coatings with the aim to provide bioactivity to the coating by the formation of hydroxyapatite. However not all the coatings were able to show bioactivity, mainly by an interaction of the anodic alginate with the ions coming from the simulated body fluid (SBF) and the BG particles. It was confirmed that all coatings imparted corrosion protection to the substrate when evaluated via potentiostatic polarization curves by immersion in Dulbecco´s MEM, also to the highly reactive magnesium alloy AZ91D, in the initial immersion stages.For the first time, in this project chondroitin sulfate (CS) was deposited by EPD. Even when the deposition was successful the coating degraded considerably fast when immersed in water based fluids. To tackle the fast degradation and impart bioactivity to CS coatings, a multilayer approach was chosen, where chitosan was used in the production of "sandwich-type" multilayers with the presence of BG in some of the layers. By this method the coating degradation was considerable reduced and the development of a bioactive composite coating was possible.The most successful coatings, in terms of degradation behavior and bioactivity, were the chitosan based coatings. The bioactive glass/chitosan (BG/Ch) system was studied in a comparative study using three different bioactive glasses. In this study all the coatings exhibited bioactivity, independently of the bioactive glass composition. The best coating in terms of homogeneity, degradability and bioactivity was produced using Bioglass 45S5®. For the system Bioglass/Chitosan considerable improvements were done compared with previous reported works, obtaining more stable suspensions and better coating homogeneity. To tailor the coating degradability and improve adhesion to the substrate, titania was added to the BG/Ch coating. In addition, simvastatin, a drug currently proposed to promote bone formation, was added to the system confirming the drug delivery potential of the coatings. Cell test studies with MG-63 human osteosarcoma cells were done on selected coatings to evaluate cell vitality and the effect of the simvastatin on cell behavior.In this work EPD has shown to be a highly versatile, low-cost and convenient method to produce organic/inorganic coatings on metallic substrates based on the chosen materials. Different approaches were studied: from single to multilayers, from coatings on flat surfaces to complex 3D structures, as well as the drug delivery potential. Coatings with tailored composition and thickness were successfully produced exhibiting the versatility of EPD as coating production technique.
Keywords: Bioglass; Electrophoretic Deposition; Chitosan; Alginate; Chondroitin sulfate; coating; Bone; Titania

Electrophoretic deposition of tetracycline hydrochloride loaded halloysite nanotubes chitosan/bioactive glass composite coatings for orthopedic implants - Radda'A, Namir S.; Goldmann, Wolfgang H.; Detsch, Rainer; Roether, Judith; Cordero-Arias, Luis; Virtanen, Sannakaisa; Moskalewicz, Tomasz; Boccaccini, Aldo R. (Surface & Coatings Technology, 2017)
Keywords: Antibacterial; Bioactive glass; Chitosan; Electrophoretic deposition; Halloysite nanotubes; Stainless steel; Tetracycline hydrochloride

Electrophoretic deposition of ZnO/alginate and ZnO-bioactive glass/alginate composite coatings for antimicrobial applications - Cordero Arias, Luis Eduardo; Cabanas Polo, Sandra; Goudouri, Ourania Menti; Misra, S. K.; Gilabert, J.; Valsami-Jones, E.; Sanchez, E.; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Materials Science and Engineering C, 2015)

Processing and bioactivity of 45S5 Bioglass®-graphene nanoplatelets composites - Porwal, Harshit; Grasso, Salvatore; Cordero Arias, Luis Eduardo; Li, Chunchun; Boccaccini, Aldo R.; Reece, Mike J. (Journal of Materials Science: Materials in Medicine, 2014)
Well dispersed 45S5 Bioglass® (BG)-graphene nanoplatelets (GNP) composites were prepared after optimising the processing conditions. Fully dense BG nanocomposites with GNP loading of 1, 3 and 5 vol% were consolidated using Spark plasma sintering (SPS). SPS avoided any structural damage of GNP as confirmed using Raman spectroscopy. GNP increased the viscosity of BG-GNP composites resulting in an increase in the sintering temperature by ∼50°C compared to pure BG. Electrical conductivity of BG-GNP composites increased with increasing concentration of GNP. The highest conductivity of 13 S/m was observed for BG-GNP (5 vol%) composite which is ∼9 orders of magnitude higher compared to pure BG. For both BG and BG-GNP composites, in vitro bioactivity testing was done using simulated body fluid for 1 and 3 days. XRD confirmed the formation of hydroxyapatite for BG and BG-GNP composites with cauliflower structures forming on top of the nano-composites surface. GNP increased the electrical conductivity of BG-GNP composites without affecting the bioactivity thus opening the possibility to fabricate bioactive and electrically conductive scaffolds for bone tissue engineering. © 2014 Springer Science+Business Media.